PERENCANAAN STRATEGIK SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Muhammad Yusuf; Rambat Nur Sasongko; Puspa Djuwita (UNIVERSITAS BENGKULU, 2017)
The objective of this research is to describe the planning of school strategies in improving the teachers’ performance. The subject of this research was the principal and teachers in Public Junior High School 1 Ketahun North Bengkulu. The method of this study was a descriptive qualitative. The data collecting technique was by interview, observation and documentation. The result of this research showed that: 1) The vision and mision team formuled by the environment considering; 2) The arrangement planning used by the several analysis; 3) the school applied the dicipline, good teachers administration and teachers partisipation; 4) The school improved the human resource development by completing the equipment and information technology.